2017
DOI: 10.1681/asn.2017020222
|View full text |Cite
|
Sign up to set email alerts
|

FXR/TGR5 Dual Agonist Prevents Progression of Nephropathy in Diabetes and Obesity

Abstract: Bile acids are ligands for the nuclear hormone receptor farnesoid X receptor (FXR) and the G protein-coupled receptor TGR5. We have shown that FXR and TGR5 have renoprotective roles in diabetes- and obesity-related kidney disease. Here, we determined whether these effects are mediated through differential or synergistic signaling pathways. We administered the FXR/TGR5 dual agonist INT-767 to DBA/2J mice with streptozotocin-induced diabetes, db/db mice with type 2 diabetes, and C57BL/6J mice with high-fat diet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 78 publications
4
105
1
Order By: Relevance
“…Our results shown that Farnesiferol B effectively inhibited the expression of inflammatory cytokines, such as MCP-1, LTB4, and TNFα. Farnesiferol B inhibited LPS-induced NF-κB activation and decreased p65 translocation in J774 macrophages, possessing similar effects as other TGR5 agonists [40]. Moreover, the anti-inflammatory effect of Farnesiferol B was blocked in RAW264.7 cells, which do not express TGR5 [21,30].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results shown that Farnesiferol B effectively inhibited the expression of inflammatory cytokines, such as MCP-1, LTB4, and TNFα. Farnesiferol B inhibited LPS-induced NF-κB activation and decreased p65 translocation in J774 macrophages, possessing similar effects as other TGR5 agonists [40]. Moreover, the anti-inflammatory effect of Farnesiferol B was blocked in RAW264.7 cells, which do not express TGR5 [21,30].…”
Section: Discussionmentioning
confidence: 74%
“…Recently, Nrf2/HO-1 has also been shown to be protective in AKI and diabetic nephropathy [37][38][39]. It has been reported that treatment with either FXR/TGR5 dual agonist INT-767 or TGR5 specific agonist INT-777 could prevent diabetic nephropathy through inducing Nrf2-mediated antioxidant generation, and reducing renal expression of oxidative stress [23,40]. We have seen similar effects in the I/R-induced mouse AKI model with treatment with FXR/TGR5 dual agonist [25].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid levels are dependent on multiple mechanisms of regulation including dietary intake and de-novo synthesis, and also on the exchange and recycling systems. Among those regulatory mechanisms, reverse cholesterol transport and its regulation by specific receptors, namely the farnesoid X receptor (FXR) and the liver X receptor (LXR), has been receiving increasing attention in relation to inflammation, especially in the pathogenesis of diabetic kidney disease [103,104] and diabetic retinopathy [105]. LXR activation was also shown to improve peripheral nerve function in rodents with obesity and diabetes-induced neuropathy, specifically by reducing endoplasmic reticulum stress or restoring myelin lipid composition; however, little is known about the anti-inflammatory effects of LXR in the setting of neuropathy [106,107].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationsmentioning
confidence: 99%
“…In the last several years, research on BAs and their receptors has been extended to their possible roles on the regulation of endothelium functions. 13 Moreover, they have also been studied in the field of ophthalmology. It was found that intermittent fasting increases generation of tauroursodeoxycholate (TUDCA), a metabolite belonging to the BAs family, and thus prevents the development of DR. 12 TGR5 activation is thought to contribute to retinal protection, but the underlying mechanisms are still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%